1989
DOI: 10.1111/j.1365-2141.1989.tb04261.x
|View full text |Cite
|
Sign up to set email alerts
|

Hairy cell leukaemia: observations on natural killer activity in different clinical stages of the disease

Abstract: Follow-up studies of natural killer (NK) cells, NK activity and antibody dependent cellular cytotoxicity (ADCC) in the course of hairy cell leukaemia (HCL) were carried out in a series of patients affected by the disease. NK activity against K562 targets was found to be high in all the patients with non-symptomatic stable disease. On the other hand, absent or extremely low NK activity was found only in patients with symptomatic progressive disease. NK activity determined in the transitional stages showed value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Although the first possibility is likely in certain leukaemias (Sorskaar et al 1986), the data presented here and other available evidence suggest that in the case of hairy cell leukaemia the depressed NK activity is a consequence of the disease, particularly as the NK activity often becomes normal when patients respond to therapy by other criteria. The amount of tumour mass is clearly import-18 ant, as seen in our patients with splenomegaly, and Demeter et al (1989) have also observed that disease activity in HCL is closely reflected in the NK function.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although the first possibility is likely in certain leukaemias (Sorskaar et al 1986), the data presented here and other available evidence suggest that in the case of hairy cell leukaemia the depressed NK activity is a consequence of the disease, particularly as the NK activity often becomes normal when patients respond to therapy by other criteria. The amount of tumour mass is clearly import-18 ant, as seen in our patients with splenomegaly, and Demeter et al (1989) have also observed that disease activity in HCL is closely reflected in the NK function.…”
Section: Discussionsupporting
confidence: 74%
“…NK-cell numbers and NK activity were unrelated to splenectomy but neither of these reports contains results obtained before splenectomy or information on the time elapsed since surgery. Demeter et al (1989) saw no effect on NK activity tested before and three to seven months after splenectomy in two patients with progressive disease.…”
Section: Discussionmentioning
confidence: 83%
“…The CD4/CD8 ratio as well as the IFN-a production of mono nuclear cells are immunological data that were found to be correlated with the remission status in HCL [23,26]. Using the functional criteria for determination of clinical stage, we dem onstrated that NK activity, ADCC as well as the CD4/CD8 ratio were correlated with the clinical stage of the disease [27,28], When reevaluating our patients clinically using the functional criteria, we observed that only peripheral blood mononuclear cells from patients with symptomatic and/or progressive dis ease proliferated in vitro in response to TNF-a, while mono nuclear cells from patients with non-symptomatic stable dis ease did not proliferate upon this stimulus [29,30], The distinction of HCL patients with stable or with progressive disease has also proven valuable in explaining the differences found in the IFN-a production of mononuclear cells [31] as well as of their TNF-a production [32], In conclusion, the above described functional criteria enable the distinction of HCL patients with non-symptomatic stable disease -not requiring therapy -from patients with symp tomatic and/or progressive disease, where treatment is indi cated. Experimental data justify the distinction of patients with non-symptomatic stable disease from those with symp tomatic and/or progressive disease.…”
Section: Discussionmentioning
confidence: 94%
“…Patients with advanced HCL have more impairment of antibody-dependent cell-mediated cytotoxicity than earlier stage patients, 15 and thus may be less capable of mounting an effective immune response against rituximabtargeted HCL cells. This may explain why patients in this series had lower response rates to rituximab than did patients in other series with less advanced HCL.…”
Section: Discussionmentioning
confidence: 99%